Knowledge map of recurrence in tenosynovial giant cell tumor: a bibliometric analysis - Gao, Pan; Ji, Shuo-Cheng; Liang, Wei; Bai, Guang-Jian; Ren, Jia-Ji; Zhong, Fu-long; Yang, Long; Wang, Jing; Xin, Bao-Quan; Liu, Tie-Long (Frontiers in Oncology, 2025)
PurposeTenosynovial Giant Cell Tumor (TGCT) is a rare benign neoplasm originating from the synovium and tendon sheath, and is characterized by a relatively high rate of recurrence following treatment. The present study was designed to identify and analyze 134 publications in this domain, with the aim of providing researchers with a comprehensive overview of the knowledge framework and research hotspots related to TGCT recurrence.MethodsA total of 134 articles concerning TGCT recurrence were retrieved from the Web of Science Core Collection. Bibliometric analysis was applied to examine various characteristics of the literature. VOSviewer and Microsoft Excel were employed to perform visualizations of temporal and geographical distributions, author productivity, thematic classifications, topic evolution, reference networks, and keyword co-occurrence.ResultsAmong the identified articles, the most frequently cited publication received 123 citations. The University of California was found to be the most influential institution in terms of citation frequency, while the United States ranked first in the number of publications. A steady increase in research activity was observed, particularly between 2021 and 2024. Nicholas Matthew Bernthal was identified as the most prolific author, with eight publications. Keywords indicating major research hotspots included “tenosynovial giant cell tumor,” “surgical treatment,” “recurrence,” “synovectomy,” and “radiotherapy.” Fourteen articles specifically addressed multimodal treatment strategies, highlighting a critical direction of research in this field.ConclusionResearch on TGCT recurrence has received increasing attention, with particular emphasis on multimodal treatment strategies. Nevertheless, the underlying biological mechanisms remain insufficiently elucidated. Further exploration of these mechanisms is warranted to enable future therapeutic advances.